Türkiye kökenli aspir tohum yağlarının transesterifikasyonu ve dizel yakıt alternatifi olarak değerlendirilmesi - Işığıgür, Aslı (Fen Bilimleri Enstitüsü, 1992)
Bitkisel yağlar enerji içeriği açısından petrol kökenli hidro karbon bileşikleri ile hemen hemen aynı düzeydedir. Buna karşın, kay naklarının yenilenebilir ve çok çeşitli oluşu sınırlı petrol rezervle ri karşısında alternatif yakıt olarak kullanımlarını daha da cazip kılmaktadır, üretilen bitkisel yağların, gıda sanayi haricinde en bü yük tüketiminin enerji alanında olabileceği ümit edilmektedir. Ancak bitkisel yağların günümüz dizel motorlarında doğrudan kullanımı sıra sında yüksek viskoziteleri nedeniyle çeşitli problemler meydana gel mektedir. Bu çalışmada Türkiye kökenli 19 aspir tohum yağı çeşidinin dizel yakıt alternatifi olarak değerlendin lebi liri iği incelenmiştir. Bu amaçla yapılan deneysel çalışmanın ilk bölümünde aspir çeşitleri nin standart yöntemlerle tohum ve yağ karakterizasyonu gerçekleştiril miştir. Bu çeşitler arasından seçilen Yenice aspir tohum yağına trans- esterifikasyon, Dinçer aspir tohum yağına ise seyreltme teknikleri uy gulanarak yüksek viskozite problemleri çözümlenmiş ve dizel yakıt al ternatifi adayları hazırlanmıştır. Metanol kullanılarak gerçekleşti rilen transesterifikasyon reaksiyonu koşullarının geniş anlamda ince lenmesi ve reaksiyon kinetiği çalışmanın ikinci ana bölümünü oluştur maktadır. Transesterifikasyon reaksiyonu ürünü metil ester ile sey reltme tekniği uygulanarak seçilen %20 Dinçer aspir tohum yağı + %80 dizel yakıtı karışım yakıtın ASTM yöntemlerine göre yakıt özellikleri belirlenerek elde edilen sonuçların standart No. 2 dizel yakıtı ile u- yum gösterdiği saptanmıştır. Çalışmanın son bölümünde ise Acadia mar ka Hercules D-2000 model gemi dizel motorunda gerçekleştirilen motor karakteristikleri ve egzoz gazı emisyonları dizel yakıtı ile karşılaş tırmalı olarak incelenmiştir.

The search for fuel alternatives originated from the fact that present sources of fossil -derived fuels are finite and their supplies will diminish gradually by the end of this century. There is, there fore, an extensive search for new energy sources among which biomass energy is given special attention and is considered as an attractive alternative to conventional energy sources. Vegetable oils in parti cular have an exceptional importance within the biomass sources since they had been used as fuel alternatives in diesel engines by the in ventor of the engine R. Diesel as early as 1892. However, the ready availability of inexpensive petroleum derived diesel fuel provided little incentive for experimenting with alternative renewable fuels for diesel engines. It was after the two consecutive OPEC oil em bargo followed by fuel shortages and rapidly increasing fuel prices that the international interest was directed towards liquid fuels of renewable origin. Liquid fuels are a vital necessity particularly for the continuation of agricultural production which mostly depends on diesel fuel. Timing of the field operations such as planting, cultivating and harvesting is especially critical. For all of these operations a readily available supply of liquid fuel is essential and vegetable oil-based fuels seem to be a convenient solution should an emergency occur. Substitution of petroleum-based diesel fuels with vegetable oil-based fuel alternatives requires the establishment of an integrated system which involves the production, processing and end use of the new fuels on a dual technology strategy. The selected oil crop must be a valuable oil export crop and must be easily culti vated while it should readily be turned into liquid fuel according to demand changes. The equipments used for processing oil for the food and export markets should also serve as the production equipment for fuel alternatives at times of crisis and emergency. Such a bio mass based technology when administered properly is important especi ally for developing countries with rich agricultural potential. Tür kiye is a developing country and 90% of the consumed crude petroleum is provided through imports which is a heavy burden on the country's agriculture based economy. Like most of the developing countries, Türkiye is endowed with rich biomass resources; with the completion of the Southeast Anatolia Project 1.6 million hectars of arid land will be irrigated and the oil crop production is estimated to incre ase by 73%. Proper selection of the oil crop for the area can easily create a valuable source for vegetable oil based liquid fuel product ion. Evaluation of such a renewable energy source seems to be the appropriate option which can help to solve the necessity of petrole um importation of the country in the future. Vegetable oils have heat contents that are approximately 90% of that of diesel fuel but their high viscosity is a major vii restriction in their direct use in diesel engines. High viscosity causes durability problems in the engine: Poor atomization of the fuel, formation of deposits on the tip of the injection nozzles and on the piston surface, contamination of the lubricating oil with un- burnt residues are the observed handicaps. Dilution, microemulsifi- cation, pyrolysis and transesterification are the four different techniques used to solve the problems encountered with high viscosity. In the dilution technique, fuel alternatives are prepared by adding certain amount of convenient vegetable oil to diesel fuel. There are different opinions in the literature about the maximum tolerable amount of vegetable oil in diesel fuel that can safely be used in the CI engines. Transesterification of the oil with short chain al cohols such as methanol and ethanol to fatty esters is the method on which researches have been focussed since 1980. Methyl esters of vegetable oils have several outstanding advantages among other new- renewable and clean engine fuel alternatives. They can readily be used without any need for modifications of. the engine; their handling, transportation and storage require no special precautions; they have the same fuel economy and engine performance as the traditional die sel fuel and they proved to be environmental friendly products of the living chemistry. Most recently in Europe, applications on the use of agricultural resources like grains and oilseeds are entering the international market as several new materials one of which is Diesel-Bi. This product is the new biofuel for CI engines which is obtained through the transesterification of soybean, rapeseed and sunflower oils with methanol. The ester fuel is now being tested for its performance in different kinds of vehicles, farm tractors and industrial mobile machinery in various countries in Europe. On the border of Europe, Türkiye has not yet attempted to establish a system pertaining the production and use of agriculture based fuel alternatives although this issue is considered in both the State Development Plans and energy programs of the country. This study is an investigation on the evaluation possibilities as a diesel fuel alternative of the oil extracted from varieties of saff lower seeds cultivated in Türkiye. Safflower can be cultivated in the same manner and processed using the same equipments as sun flower. But, although sunflower is one of the basic raw materials of the edible oil industry, safflower is an oilseed of minor impor tance for the same industry in Türkiye. It is cultivated in the Central Anatolia and Thrace regions of the country within the scope of certain projects that are supported by the Ministry of Agricultu re and Forestry. Therefore, 17 varieties of safflower seed were pro vided from Eskişehir Agricultural Reasearch Institute and two varie ties (Yenice and Dinçer) that were advised to be grown in the Thrace region by the same institute were provided from Tekirdağ Leading Farmer Project. Characterization of the safflower seed samples was the first step taken in the experimental procedure; the weight, length and hull contents of the seeds were calculated as the average of measurements taken with 50 seeds. Moisture and oil contents of the cultivars were determined according to standard methods and the variation in moisture content was found to be 7-9% while the oil content varied between 18-35%. Following the characterization of the seeds, the 17 cultivars that were provided in smaller amounts were ground mechanically and the oil was extracted in a Soxhlet viii extractor using n-hexane as the solvent. Oil from Yenice and Dinçer varieties which were purchased in larger amounts was extracted accord ing to cold press technique in an oil processing factory. Some tech nological characteristics of the 19 oil samples were then determined according to standard methods for fat and oil analysis. Their fatty acid compositions were analyzed using the gas-liquid chromatography technique and within the cultivars, 5.154.2 was found to be the high oleic variety The two varieties, Yenice and Dinçer, that were grown in the Thrace region and that could be provided in larger amo unts than the others, the high oleic variety 5.154.2 and the edible grade, refined safflower oil of Swiss origin (Saflor) were selected for applying the transesterif i cation technique for viscosity reduct ion. Taking the previous transesterif i cation applications into consideration, the reactions were performed in a three-necked flask equipped with a reflux condenser and a contact thermometer. Reaction temperatures were held constant within a range of + 1°C and the free neck of the flask was used for taking samples at certain time inter vals during the experiments. Transesterif i cation reactions were rea lized using methanol as the alcohol and potassium hydroxide as the reaction catalyst. Reaction mixtures were heated on a magnetic hea ter and stirer to a few degrees above the boiling point of methanol where condensation first begun. At the end of each reaction, the reaction mixtures were allowed to cool down to room temperature then taken into a separatory funnel where the ester and glycerol layers separated. The excess methanol in the ester layer was eliminated in a rotating evaporator under reduced pressure. The crude ester was then dissolved in petroleum ether, washed with water, acidified using glacial acetic acid until pH=7 was reached, washed several times with water, dried over anhydrous sodium sulphate and the petroleum ether was removed in the rotating evaporator under reduced pressure hence revei ling the refined methyl ester product. The conversion of the vegetable oil to its monoester, diglycerides and monoglycerides was analyzed with Iatroscan TLC/FID analysis where the FID was operated with hydrogen and air flow rates of 160 and 2000 ml/min respectively. One ml samples that were taken in certain time intervals from the reaction mixture were quenched in 1 ml cold water to seize the react ion and were then centrifuged. A drop of the oil layer was weighed on an analytical balance and dissolved in chloroform to give a con centration of 3.0 mg of oil per ml of solution. Solutions to be analyzed were applied on Type SIII Chromarods with an automatic sample: spotter in amounts of 1.6 yl of solution per rod. The rods were developed in a glass tank containing petroleum ether, diethyl- ether and acetic acid (70:30:2) for 20 minutes, kept at room tempera ture for 5 minutes, dried at 110°C in a vantilated oven for 5 minutes and placed on the Iatroscan TH-10 MK IV analyzer. The signals produ ced were sent and evaluated by a recorder-integrator system, the Iat- rocorder TC-11. The variables affecting the monoester yield during transesterification reaction such as the molar ratio of alcohol to vegetable oil, reaction temperature and duration, type and amount of the catlayst used were investigated as the next step in the experi mental work. The stoichiometry of the transesterification reaction requires 3 moles of alcohol per mole triglyceride to give 3 moles fatty ester and a mole of glycerol. To determine the effect of molar ratio Yenice safflower oil was transesterified at 1:3, 1:4, 1:5, 1:6, 1:7 vegetable oil-methanol molar ratios using Yl by weight of oil KOH as catalyst and keeping the reaction temperature at 69 + 1°C. IX The results confirmed the -importance of using an excess amount of al cohol and at 1:7 molar ratio the methyl ester yield was 97% in 16 mi nutes. To determine the effect of the amount of alkali catalyst used on the reaction, the results of the reactions with 0.5%, 1% and 2% of KOH were compared at 1:7 molar ratio and at 69 + 1°C. One % by the weight of oil was found to be the appropriate amount for the reaction, Changing the alkali catalyst from 1% KOH to 1% NaOH proved that KOH was superior under the applied conditions. Although alkali alcoholy- sis of vegetable oils is normally conducted near the boiling point of the alcohol used, lower reaction temperatures were also investigated for their effect on the performance of the transesteriffcation react ion. Reactions were performed at 49 + 1°C, 59 + 1°C and 69 + 1°C at the previously determined conditions of 1:7 molar ratio and 1% by weight of oil KOH catalyst. It was observed that ester yield_was po sitively affected by the increase in temperature. Hence, 69 + 1°C was found to be the most suitable reaction temperature for maximum conversion, of the triglyceride. Applying the predetermined conditi ons to the previously chosen oils for investigation was the last step of the experiments regarding the transesterification reaction. Saflor (the refined, nutritional grade safflower oil) showed the fastest conversion to the methyl ester followed by Yenice, 5.154.2 and Dinçer varieties. The slower conversion observed in Dinçer vari ety was attributed to its higher free fatty acid content which inter feres with the catalytic activity. The kinetics of the Yenice saf flower seed oil-methanol transesterification reaction was briefly studied as the next step in the experimental procedure. The optimum reaction conditions were: reaction period=18 minutes; reaction catalyst=KOH (1% by weight of oil); reaction temperature=69 + 1°C and vegetable oil: methanol molar ratio=l:7. Depending on the decre ase in the amount of triglyceride and on the conversion percentage of triglyceride (%x) calculated from the results obtained with Iatro- scan analysis, degree of the reaction was determined as n=l and rate constant as k=0.222 dak-l. The activation energy for this reaction was determined using the experimental results obtained for the react ion at 49 + 1°C, 59 + 1°C and 69 + 1°C and was calculated as E=56.03 kJ/mol. In the second part of this study, the fuel alternatives were prepared applying the two techniques for viscosity reduction namely the transesterification and dilution. Considering the fatty acid compositions of the Yenice and Dinçer varieties, transesterification reaction was applied in a larger scale to the Yenice variety while Dinçer variety was diluted by adding 10-90% by volume oil to commer cial Grade No.2-D diesel fuels The fuel alternatives were then in vestigated for their viscosities and a dramatic decrease in viscosity was observed both with the methyl ester product and with the 10 and 20% blends compared to the parent vegetable oil. The kinematic vis cosity values for those three fuel canditates also lied between the limits specified for Grade No. 2-D diesel fuel. The fuel property tests which were performed on the ester and blend fuels and their respective ASTM numbers are: (a) Density (ASTM D 4052}, (b) Refrac tive Index (ASTM D 1218), (c) Hydrogen Content (ASTM D 3701), (d) Surface Tentsion (ASTM D 971), (e) Cetane Number (ASTM D 613), (f) Gross Heating Value (ASTM D 240), (g) Flash Point (ASTM D 93), (h) Pour Point (ASTM D 97), (i) Sulphur Content (ASTM D 4294), U) Corrosion (ASTM D 130). The methyl ester fuel had better cetane and flash point values which were an advantage over the commercial diesel fuel while its density, refractive index, surface tension and hydrogen contents were very close to diesel fuel. The gross heating value of the ester fuel was 11.5% lower and its pour point was within the limits given for Grade No. 2-D diesel fuel. Within the blend fuels, an increase in the amount of Dinçer oil in the diesel fuel resulted as an increase in the density of the blend fuel. During the cetane number measurements, blends containing over 40% of oil caused trouble in the CFR test engine. As a result of the ASTM fuel property tests the fuel alternatives ME (methyl ester fuel), D10 and D20 (10 and 20% blends) having similar properties as Grade No. 2-D diesel fuel were selected for the engine performance tests. Engine tests, using reference diesel fuel and the fuel alternatives were performed on an Acadia-Hercules Model AD-20 four cylinder marine type Diesel engine. Exhaust gas emissions were continiously measured with Horiba, Model Mexa-534 GE digital exhaust emissions analyzer. Particulates, that gave several problems during emission measurements were eliminated by using a filter system composed of various filtering media. Re sults of the engine performance tests can be summarized as follows: Under half load conditions, a slight decrease was observed in the power, torque, mean effective pressure and thermal efficiency values while there was an increase in the specific fuel consumption with the D 20 blend fuel. At full load, an increase in the specific fuel consumption was observed with both the methyl ester fuel and D 20 blend fuel compared to reference Grade No. 2-D diesel fuel. The hig her thermal efficiency than the diesel fuel obtained with methyl es ter fuel at this load was attributed to its higher excess air coeffi cient. All the other characteristic values for both the ester fuel and the blend fuel were very close to those for diesel fuel itself. D20 gave similar CO and HC emissions with diesel fuel at half load condition while there was a slight decrease in the CO and HC emis sions at full load condition compared to diesel fuel. On the other hand, a dramatic decrease compared to reference diesel fuel in both CO and HC emissions were observed with the ester fuel at full load position.
Transesterification of safflower seed oil of Turkish origin and its evaluation as a diesel fuel alternative
Tez (Doktora)-- İTÜ Fen Bil. Enst., 1992.
Keywords: Aspir; Dizel yakıtlar; Tohum yağları; Transesterifikasyon; Türkiye; Yakıtlar; Safflower; Diesel fuels; Seed oils; Transesterification; Turkey; Fuels